Modelagem física de plataformas de transferência de cargas reforçadas com geogrelhas sobre colunas granulares encamisadas utilizando solos transparentes - Vieira, Andréa Maria Pereira (2024)
One effective approach to address the challenges posed by constructions on soft soils is the use of embankments supported by granular columns. These columns offer advantages such as enhancing soil bearing ability, minimizing drainage pathways, and mitigating settlements. It's customary to incorporate a layer of granular material atop the columns, akin to practices in pile-supported embankments, serving as a drainage base and aiding in load transfer to the superstructures. Nonetheless, the mechanisms and behaviors associated with load transfer platforms on granular columns may diverge from those of pile-supported structures, owing to the columns' lower stiffness compared to piles. Understanding these mechanisms in geotechnical contexts is a complex task, which requires a comprehensive view of the problem. The advent of transparent geotechnical materials, mirroring real soil characteristics, enables thorough problem modeling with extensive visualization and precise displacement and deformation quantification, thus helping system behavior analysis and interpretation. In this context, this study aimed to develop a scaled physical model of an embankment on soft soil reinforced with encased granular columns, employing a stratified system of transparent soils. The soft soil was simulated using a 150 mm layer of transparent synthetic clay, made with Laponite RD® and Sodium Pyrophosphate Decahydrate (PSD), reinforced with two encased granular columns of 50 mm in diameter. The granular base layer used as a load transfer platform (LTP) was composed of alternating layers of transparent synthetic sand and geosynthetic reinforcement. This model helped soil behavior analysis using digital image correlation (DIC), fostering comprehension of stress transfer mechanisms in embankment systems with load transfer platforms supported on improved soft soil with encased granular columns. Additionally, it evaluated the impact of geogrid use as reinforcement. Based on the results obtained, it was concluded that the materials used were suitable for simulating the problem. Overall, the use of geogrids was able to reduce vertical displacements and the part of load transferred to the soft soil.